Injury of the dentato-rubro-thalamic tract in patients with cerebellar infarct: Case report - Jang, Sung Ho (Medicine (Baltimore), 2017)
RATIONALE: Several studies using diffusion tensor tractography (DTT) have reported on injury in the dentato-rubro-thalamic tract (DRTT) in patients with brain injury. However, there is no study of injury in the DRTT following cerebellar infarct. We report on patients with injury in the DRTT following cerebellar infarct, demonstrated on DTT. PATIENT CONCERNS: Three patients with cerebellar infarct were enrolled in this study. Diffusion tensor imaging data were acquired at 3 weeks (patient 1) and 2 weeks (patients 2 and 3) after onset and the DRTT was reconstructed. The Scale for Assessment and Rating of Ataxiaand the Functional Ambulation Category were used for evaluation of ataxia and gait function. DIAGNOSES AND OUTCOMES: With clinical evaluation, patient 1 scored 18, patient 2 scored 22, and patient 3 scored 28 points on the Scale for Assessment and Rating of Ataxia. On the Functional Ambulation Category patient 1 scored 2, patient 2 scored 2, and patient 3 scored 1 point. DRTT abnormalities were as follows: discontinuation (the upper portion of the left DRTT in the patient 1), narrowing (the lower portion of the left DRTT in patient 2, and the whole right DRTT in the patient 3), and nonreconstruction (the left DRTT in the patient 3). LESSONS: Using DTT, we demonstrated injury in the DRTT in 3 patients with severe ataxia following cerebellar infarct. We believe that evaluation of the DRTT would be helpful in patients who develop ataxia following cerebellar infarct.